Potencialização do rendimento do gerador a relutância chaveado empregando técnica de rastreamento associada a controle de tensão otimizado - Araújo, Wanderson Rainer Hilário de (2020)
This work presents the potentialization of the efficiency of the Switched Reluctance Generator (GRC) submitted to the control of the output voltage. The efficiency is enhanced by using tracking technique acting on the switching angles of the power converter. As it is a DC machine, the control of the output voltage is applied to adapt this value to DC-AC conversion systems and load controllers. The PID controller is used and, because it is a controller with only one output, other quantities are not contemplated by the performance of the controller. In this work, there is an interest in enhancing the performance of the GRC to make this type of machine more attractive for generating electricity in distributed systems and in installations without connection to the main distribution network. Therefore, in parallel to the PID controller, a tracking technique is applied to the GRC performance with a disturb and observe algorithm. Other procedures are presented, such as obtaining an inductance surface to improve the mathematical and computational modeling of the generator, in addition to the development of an indirect conjugate detection system. Simulation and experimental results are presented for validation and discussion of the proposed study.